Relationship between TNF-α levels and psychiatric symptoms in first-episode drug-naïve patients with schizophrenia before and after risperidone treatment and in chronic patients - Chen Lin (BMC, 2021)
Abstract Background The influence of antipsychotic drugs on tumor necrosis factor-α (TNF-α) levels is unclear, and there is no consensus on the association between TNF-α and psychotic symptoms. This study aimed to investigate the differences in TNF-α levels and clinical correlations in first-episode drug-naïve (FEDN) patients with schizophrenia before and after treatment and in chronic patients. Methods A total of 103 (51 FEDN and 52 chronic) patients and 114 healthy controls were recruited. Demographic and clinical data, including TNF-α levels, were recorded. We used the Positive and Negative Syndrome Scale (PANSS) to measure the psychopathology of all patients. Results TNF-α levels before treatment were significantly higher in FEDN patients than in chronic patients and healthy controls. No significant sex differences were found in the TNF-α levels of patients with schizophrenia. The TNF-α levels before treatment were significantly positively related to changes in PANSS negative symptoms in FEDN patients. The TNF-α levels in chronic patients were significantly negatively correlated with the general psychopathology subscales and PANSS total scores. Conclusions Increased TNF-α levels in FEDN patients and their correlation with psychopathology indicate that inflammatory cytokines may play a crucial role in the etiopathogenesis of schizophrenia, and inflammation-directed therapy may, therefore, improve negative symptoms.